PENGARUH DISIPLIN KERJA, MOTIVASI, DAN PENGEMBANGAN KARIER TERHADAP KINERJA KARYAWAN PADA PD.BKPD (BANK PASAR) KABUPATEN DEMAK - Evidya rukaya, 12.05.51.0201; Yunianto, Askar (Students Journal of Economic and Management, 2016)
This study aims to determine and describe the influence of labor discipline , motivation and career development to employees performance at PD.BKPD Demak . Its population is the employees amounted to 100 employees . Given a population of 100 employees , the number of the population is eligible to be taken all sampled. In this study , the study population refers to all employees on PD.BKPD Demak . Samples taken as many as 100 respondents using data collection techniques by spreading the questionnaire .The sequence individually from each of the variables that most influence on employee performance in PD.BKPD Demak is the motivation variable work with a regression coefficient of 0.390 , and career development variables with a regression coefficient of 0.304 . While the variables that affect the lowest is work discipline variables with a regression coefficient of 0.233 . This equation models have F count equal to 51.240 and with a significance level of 0.000 . It shows that the independent variables in this study jointly influence the dependent variable is the performance of employees . Keywords : Work Discipline , Motivation , Career Development , Employee Performance .